LONG-LIFE LEARNING : PREPARING FOR JOBS THAT DON'T EVEN EXIST YET - Weise, Michelle R., author. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2021)
"A visionary guide for the future of learning and work Long Life Learning: How to Prepare Yourself for Jobs That Don't Even Exist Yet offers readers a fascinating glimpse into a near-future where careers last 100 years, and education lasts a lifetime. The book makes the case that learners of the future are going to repeatedly seek out educational opportunities throughout the course of their working lives -- which will no longer have a beginning, middle, and end. Long Life Learning focuses on the disruptive and burgeoning innovations that are laying the foundation for a new learning model that includes clear navigation, wraparound and funding supports, targeted education, and clear connections to more transparent hiring processes. Written by the visionary chief innovation officer of Strada Education Network's Institute for the Future of Work, the book examines: How will a dramatically extended lifespan affect our careers? How will more time in the workforce shape our educational demands? Will a four-year degree earned at the start of a 100-year career adequately prepare us for the challenges ahead? Perfect for anyone with an interest in the future of education and Clayton Christensen's theories of disruptive innovation, Long Life Learning provides an invaluable glimpse into a future that many of us have not even begun to imagine"--